A national physician survey on prescribing syringes as an HIV prevention measure. - Macalino, G E; Sachdev, D Dhawan; Rich, J D; Becker, C; Tan, L J; Beletsky, L; Burris, S (Substance abuse treatment, prevention, and policy, 2009)
Access to sterile syringes is a proven means of reducing the transmission of human immunodeficiency virus (HIV), viral hepatitis, and bacterial infections among injection drug users. In many U.S. states and territories, drug paraphernalia and syringe prescription laws are barriers to syringe access for injection drug users (IDUs): pharmacists may be reluctant to sell syringes to suspected IDUs, and police may confiscate syringes or arrest IDUs who cannot demonstrate a "legitimate" medical need for the syringes they possess. These barriers can be addressed by physician prescription of syringes. This study evaluates physicians' willingness to prescribe syringes, using the theory of planned behavior to identify key behavioral influences.
Keywords: Attitude of Health Personnel; Data Collection; Female; HIV Infections; Humans; Male; Middle Aged; Physicians; Prescriptions; Professional Practice; Substance Abuse, Intravenous; Syringes